Pengaruh Kapasitas Layanan dan Pembiayaan Kesehatan terhadap Peningkatan Angka Harapan Hidup di Provinsi Nusa Tenggara Barat - Nur Rahmi Luthfiana; Syabrina Indah Thania; Putri Muthia Iskandar; Revalia Anggiani Maulidina; Nessa Zaira Dharmawan; Fitri Amalia (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
Life expectancy (AHH) serves as a fundamental benchmark for evaluating community welfare and the success of human capital development. This study aims to analyze the influence of infrastructure capacity and fiscal support on AHH achievement in West Nusa Tenggara Province. Using a quantitative approach and 2024 data, this study examines the impact of the number of Public Hospitals, the availability of medical personnel, and the allocation of the Regional Budget (APBD) for the health sector across all districts/cities. Multiple linear regression analysis yielded interesting results. Simultaneously, all three variables influenced AHH, but partial testing revealed that physical infrastructure and the quantity of medical personnel did not significantly impact life expectancy. Conversely, health financing through the APBD was the only determinant shown to have a significant influence. This indicates that the availability of facilities alone is insufficient without the support of effective financial management. Therefore, this study concludes that a shift in policy focus from mere physical expansion to optimizing more strategic budget management is necessary to ensure quality health services for the community.